EFEKTIFITAS PEMBERIAN REWARD DALAM BENTUK MAKANAN UNTUK MENGURANGI PERILAKU MENGGANGU TEMAN KETIKA BELAJAR - RINO YUNIDA Putra (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This research begins from issues which researchers found during the initial research to hyperactive children which have behavioral disorders such as disturb their friends when learning. The child often take their friend book, disturb their friends while studying in the classroom, leg shakes as if listening to music, angry when the desire is not obeyed, often borrow the other people's things by force, exit and entry of the classroom without the teacher's permission. This study have a purpose to prove the effectiveness granting rewards to reduce the disruptive behavior friend when studying in class in hyperactive children in the fourth grade SLB Hikmah Miftahul Jannah Padang. Design research in this field using the experimental single case that multiple baseline design. Multiple baseline design is a design that has internal validity better than other designs. Where this design provides tight control of the intervention condition and memunkinkan results show causality between the independent variables and the dependent variable. Variations used in the study using multiple baseline design cross conditions. Kata Kunci : Reward yang di gunakan, Multipel baseline, perilaku yang di kurangi